Position paper: Using EdTech to support teacher education and professional development in low- and middle-income countries (internal working paper). - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2020)
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF

Tanzanian Teachers’ Experiences of Teaching With Technology: Recommendations for policy and practice - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2022)
This policy brief reports on a teacher survey in Tanzania (July–November 2021) that EdTech Hub commissioned HakiElimu to conduct in order to inform the government’s ongoing national school-based TCPD reform. The survey items were taken from a landmark global survey of 20,000+ teachers’ reflections, experiences, and challenges concerning EdTech access and use, teaching and learning, and professional development over the preceding year, reported by a team from T4 Education and EdTech Hub. Keywords: Educational technology; learning outcomes; teacher needs; teacher professional development; teacher voice; technology access An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Uzoefu wa Walimu katika kufundisha kwa kutumia teknolojia nchini Tanzania Mapendekezo Juu ya Sera na Utekelezaji - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2023)
This is a Swahili version of the policy brief Teachers’ Experiences of Teaching With Technology in Tanzania: Recommendations for policy and practice published in October 2022. Muhtasari huu wa masuala ya kisera unatoa ripoti ya utafiti wa walimu nchini Tanzania (Julai-Novemba 2021) ambao EdTech Hub iliagiza HakiElimu kuufanya ili kuchangia taarifa itakayosaidia mchakato endelevu wa serikali kuleta mageuzi ya MEWAKA katika ngazi za shule na vituo vya walimu. Dodoso zilichukuliwa kutoka katika uchunguzi wa kihistoria wa kimataifa uliohusisha takriban walimu 20,000+ , kuhusu uzoefu na changamoto zao katika ufikiaji na matumizi ya EdTech, ufundishaji na ujifunzaji, na maendeleo ya kitaaluma katika mwaka 2021, iliyoripotiwa na timu kutoka T4 Education na EdTech Hub. Maneno muhimu: teknolojia ya elimu; matokeo ya kujifunza; mahitaji ya mwalimu; mafunzo endelevu ya taaluma ya ualimu; sauti ya mwalimu / Kauli ya mwalimu; ufikiaji wa teknolojia An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Reflections on technology, teaching, learning, and professional development: Findings from a teacher survey in Tanzania - Koomar, Saalim; Hennessy, Sara; Zubairi, Asma; Kindoli, Robert; Kreimeia, Adam (African Educational Research Journal, 2022)
This paper presents findings from a survey of 774 government school teachers across Tanzania over the period 2020-2021. The aims were to capture teachers' recent experiences concerning (1) access and use of technology; (2) any student learning losses observed, and teachers' recommendations to address lost learning; and (3) experiences and needs concerning teacher professional development (TPD). Key findings were (1) forty percent of teachers reported that their school lacked access to any form of technological device, with almost half stating they never used digital technologies for teaching and learning purposes. (2) Almost half of the teachers perceived that girls' learning suffered more than boys, and more than 60% of teachers believed learners from the financially poorest households suffered the greatest learning losses. (3) Teachers in Tanzania engaged in very little TPD and wanted increased support. The key differences across teacher groups were further examined by demographic factors, with notable differences apparent between urban and rural teachers, teachers with different levels of experience and different qualification levels. Recommendations are presented to stakeholders across the education ecosystem, including policymakers, school leaders, TPD designers, teachers, and researchers. The findings inform a national technology-mediated TPD programme in Tanzania.
Keywords: Access to Computers; Elementary School Teachers; Faculty Development; Foreign Countries; Gender Differences; Learning Processes; Pedagogical Content Knowledge; Poverty; Public School Teachers; Rural Urban Differences; Secondary School Teachers; Social Differences; Teacher Attitudes; Teacher Characteristics; Teacher Qualifications; Teacher Surveys; Teaching Experience; Teaching Methods; Technological Literacy; Technology Integration; Technology Uses in Education; _r:AddedByZotZen

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Technology and Teacher Professional Development in Tanzania: Research instruments pack - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chachage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
This pack contains links to research instruments developed by EdTech Hub, Aga Khan University, and Tanzania Institute of Education for a study investigating the impact of a national teacher professional development programme on primary-level learning outcomes. The tools have been developed iteratively, with substantive piloting having taken place, both in workshop settings and in schools. They draw on good practice examples, such as the World Bank’s TEACH tool for classroom observation and other research projects the team have worked on. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit.
Keywords: _r:AddedByZotZen

Teknolojia na maendeleo ya taaluma ya walimu nchini Tanzania: Zana za utafiti - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chacage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Aga Khan University, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza athari za programu ya maendeleo ya kitaaluma ya walimu kwenye matokeo ya masomo ya ngazi ya msingi. Zana zimetengenezwa na kufanyiwa majaribio makubwa katika warsha, pamoja na shuleni. Zana hizi zimetengenezwa kwa kuzingatia mifano mizuri kama vile zana ya Benki ya Dunia ya TEACH ya uchunguzi wa darasani, pamoja na miradi mingine ya utafiti ambayo timu imefanyia kazi. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao.
Keywords: _r:AddedByZotZen

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen